Evaluation of C-reactive protein levels as biomarkers for immune response among septic patients in Yemen - Talal Yahya Alqahtani; Abdulsalam Halboup; Ahmed S. Hudna; Ibrahim Al-Subol (Zenodo, 2024)
Background: Sepsis is a severe and potentially fatal illness characterized by an uncontrolled immune response to infection, resulting in significant morbidity and mortality. This study aimed to evaluate C-reactive protein (CRP) levels as biomarkers for immune response among septic patients in Sana'a, Yemen and assess their correlation with other clinical factors. Methods: A cross-sectional study was conducted among 100 septic patients admitted to three major hospitals in Sana'a city between January and April 2024. Patients' demographic data, CRP levels, cortisol levels, complete blood count (CBC) results, and bacterial isolates were collected and analyzed using SPSS version 27. Spearman's correlation and logistic regression tests were employed to assess relationship between variables. Results: Among the 100 patients, 56.0% were male and 48.0% were over 40 years old. Elevated CRP levels were seen in 95.0% of patients, with 67.0% showing elevated cortisol levels. Klebsiella spp. was the most common bacterium isolated (24.1%). Significant correlations were found between CRP levels and age (r = 0.343, p < 0.001), cortisol levels (r = 0.209, p = 0.037), hemoglobin (r = -0.401, p < 0.001), platelet count (r = -0.254, p = 0.011), and red blood cell count (r = -0.277, p = 0.005). Multivariate logistic regression identified lower hemoglobin levels as a significant predictor of higher CRP levels (OR: 0.424, 95% CI: 0.203-0.887, p = 0.023). Conclusion: This study highlights the clinical relevance of CRP levels in assessing immune response and disease severity in septic patients. Lower hemoglobin levels were consistently associated with higher CRP levels, highlighting potential implications for patient management and treatment strategies in sepsis.